Vertebrates in the “Palude di Torre Flavia” Special Protection Area (Lazio, central Italy): an updated checklist - Corrado Battisti; Michele Cento; Fulvio Fraticelli; Steven Hueting; Sergio Muratore (Natural History Sciences, 2021)
Here we present the checklist of the vertebrates of the “Palude di Torre Flavia”, a protected area in Tyrrhenian central Italy (Special Protection Area according to the Directive 2009/147/EC). To draw up the checklist, we collated all the records found in the literature, in private collections, and in the Ornitho.it website database, as well as sporadic historical observations. We obtained evidence documented between 1981 and 2020 for 291 taxa of which 259 native, 26 allochthonous and 6 domesticated species in 5 classes: 5 actinopterygians (4 native species and 1 allochtonous), 2 amphibians, 20 reptiles (11 native species and 9 allochthonous; the last being all freshwater terrapins), 244 birds (including 14 non-native taxa and 6 domestic forms) and 20 mammals (including 2 allochthonous). Forty-three species are listed as of conservation concern on a national scale. The area has shown to be an important biodiversity hotspot, and a major stopover site for migrating birds. Further research should be focused on some still poorly investigated taxonomic groups, in particular: Actinopterygii, Amphibia Salamandridae, Carnivora Mustelidae, and Chiroptera.